Predictors of nature of ingested foreign bodies in children & assessment of operative outcomes. (October 2018) - Arora, Rubeena; Kumar, Sunil; Singh, Gautam Bir
Abstract: Objective: To examine sensitivity/specificity of history & radiology to identify ingested foreign body (FB) and develop a protocol for management of ingested FBs in paediatric patients; to assess outcomes of removal of lithium button battery foreign body (LBBFB). Methods: Retrospective review. Children presenting to ENT emergency with suspected FB ingestion underwent rigid esophagoscopy and FB removal. Average age, number of attempts, duration of ingestion, success rate, and complications were analysed. Results: Cases of coin/LBBFB ingestion: 916/70. Mean age: 5.8/2.03 years (p < 0.001). Average duration of ingestion: 37/9.5 h (p < 0.001). Patients below 3: 31.3/62.8% (p < 0.001). Suggestive history/radiological signs: 100%/100%, 75.7%/98.6% (p < 0.0001). Site of impaction cricopharynx: 60.3%/74.3% (p = 0.02). LBBFB group: Successful removal in 1st attempt: 66 (94.3%). Cases requiring multiple attempts due to impaction: 4 (5.7%). Parenteral steroids were administered before successful reattempt. No relation was found between duration of ingestion/impaction. Five (7.1%) cases developed complications. Average follow-up duration: 13.59 months. Conclusions: Children <3 years with vague history of FB ingestion and suggestive chest x-ray should be sent urgently for FB removal. Parenteral pre-and postoperative short course steroid use may be considered to improve outcomes.